Analyzing the impact of inflation, exports and unemployment on economic growth in indonesia: A fixed effects least squares dummy variable panel regression approach - Harismahyanti A., Andi; Nur’eni, Nur’eni (Priviet Social Sciences Journal, 2025)
This study explores the impact of inflation, exports, and unemployment on economic growth in Indonesia from 2019 to 2023 using a Fixed Effects Model Least Squares Dummy Variable (FEM LSDV) panel regression approach. The analysis incorporates both province-specific and time-specific effects to provide a comprehensive understanding of the dynamic relationships between these variables and their collective influence on Indonesia's economic growth. The results indicate that exports have a significant positive effect on economic growth, consistent with existing literature highlighting the importance of exports in driving economic performance. In contrast, inflation and unemployment were not found to have statistically significant impacts, possibly due to the model’s focus on regional and temporal variations. The study furthermore reveals significant regional disparities in economic growth, with provinces like DKI Jakarta, Banten, and Kalimantan Timur showing negative growth, while others, such as Sulawesi Selatan and Gorontalo, experienced above-average growth. The FEM LSDV model demonstrates strong explanatory power, with an R-squared value of 0.9162, indicating that it effectively captures the variability in economic growth across regions and over time. The findings suggest that promoting export-driven growth and addressing regional imbalances are key strategies for fostering sustainable economic development in Indonesia.